'A forest of urbanization': Camp Metropolis in the edge areas. (3rd April 2019) - Alkhalili, Noura
ABSTRACT: This article examines two issues located at the core of the Palestinian struggle: Jerusalem and the refugee camps. I aim to trace the forced encounter staged at these two crucial sites of contestation, while looking at the collisions/interactions that occur between them, and the types of geographies that are produced within an experience of abandonment. This is done by exploring how the colonized re-produce their own spaces after being systematically displaced either as refugees in 1948 or as Jerusalemites due to the ongoing 'Judaization' of Jerusalem – particularly following the construction of the Separation Wall – in places that are forced to become edge areas. The article focuses on the period following the Oslo Accords and the establishment of the Palestinian Authority (PA) – a period characterized by the introduction of neoliberalism and the acceptance of an urban apartheid. In this article, I will show the central role of the marginalized refugee camps in how they have contributed to the frenetic urbanization that is serving the displaced Palestinian Jerusalemites. In these edge areas, the camp has re-adjusted its position and shifted from being at the fringes of the city to the center of the edge areas; it has become what I call a 'Camp Metropolis'. This article investigates two case studies: Kufr Aqab/ Qalandia and Shu'faat areas.